Solar wind magnetosonic mach number as a control variable for energy dissipation during magnetic storms - Bagheri, Fatemeh; Lopez, Ramon E. (Frontiers in Astronomy and Space Sciences, 2022)
During the main phase of many magnetic storms the solar wind Mach number is low and IMF magnitude is large. Under these conditions, the ionospheric potential saturates, and it becomes relatively insensitive to further increases in the IMF magnitude. On the other hand, the dayside merging rate and the potential become sensitive to the solar wind density. This should result in a correlation between the intensity of the auroral electrojets and the solar wind density. In this study we provide a sample of 314 moderate to strong storms and investigate the correlation between Dst index and the energy dissipated in the ionosphere. We show that for lower Mach numbers, this correlation decreases. We also show that the ionospheric indices of the storms with the lower Mach number are less correlated to the geoeffectiveness of the solar wind during these storms.